A new domain decomposition FDTD technique for simulating electromagnetic penetration into buildings - Abd-EI-Raouf, Hany Ehsan (2005)
We developed two techniques for solving the problem of penetration of electromagnetic waves into large buildings. The first technique based on hybridizing the new FDTD domain decomposition and the Method of Moments (MoM), for solving the problem due to an arbitrary excitation. The hybrid technique enables us to efficiently handle wire type configurations using a MoM type of code, while we use the proposed domain decomposition FDTD method to analyze inhomogeneous structures, such as buildings with doors, windows and electronic. The second technique based on hybridizing the Yee algorithm with the higher order FDTD "M3d24" scheme. So that, the Yee algorithm will be applied to the external inhomogeneous subdomain while the M3d24 scheme will be applied to the large internal subdomain in which we can use low resolution grid that can be handled using the available computer resources.